Recent Advances in Big Data and Deep Learning Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, Held at Sestri Levante, Genova, Italy 16-18 April 2019 /: Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, Held at Sestri Levante, Genova, Italy 16-18 April 2019. (c2020) - Unknown
No abstract available